(untitled) (World Bulletin of Public Health, 2026)
This article analyzes the role of digital technologies in the formation of creative competence in the process of training primary school teachers and suggests mechanisms for implementing innovative approaches in the pedagogical process. The conditions for the development of the components of creative competence of future primary school teachers are analyzed. Creative competence depends not only on pedagogical knowledge, but also on the ability to think creatively, based on a practical approach.